Modal Analysis of Steel-Concrete Composite Floor in the RFEM 6 Software - Pędziwiatr, Klaudia; Abramowicz, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Using FEA programs, the structure`s modal analysis itself is not complicated. However, in the case of a steel-concrete composite floor, a difficulty arises in the composite behaviour representation. In typical FEA programs, it is not possible to directly insert the composite structure, so the components cooperation has to be represented by substitute methods. In this case, functions such as an orthotropic material, modelling the beams as ribs interacting with the surface (concrete slab) and the use of eccentricities are useful. Besides the modelling methods in RFEM 6, a modal analysis based on the example of a floor is presented. The results are shown and the floor is assessed according to the described guidelines and classification. Based on the fundamental frequency (6.81 Hz), modal mass (58888 kg) and damping (4%), a floor acceptance class C was identified, which is suitable for the assumed office use of the area.
Keywords: steel-concrete composite floor; RFEM; natural frequency; dynamic characteristics; composite behaviour